Citopatologia por Punção Aspirativa com Agulha Fina no Fibroadenoma de Mama. Estudo de 88 Casos - Alves, Elizabeth de Carvalho (2023)
The value of cytology in the preoperative diagnosis of fibroadenoma of breast is stressed. Zajicek's technique was employed in 88 smears obtained by aspiration from surgical specimens or directly from patients. The smears were stained by modified Shorr's method and cyto-histopathologic correlation was stablished. After discussing the cytologic criteria the authors show that it is possible to diagnose mammary neoplasias by this method, emphasizing the importance of the high incidence of fibroadenomas.